Analisis Semiotika Iklan E-Commerce “Dekatkan Yang Jauh, Kirim Yang Bermakna” di Media Sosial - Kurnia Ramadhan; Rosita Anggraini (Bandung Conference Series: Journalism, 2023)
Abstract. The purpose of this study was to examine the meaning of Tokopedia's ad "Closer To The Far, Send Meaningful" on Youtube using Roland Barthes semiotics. The concepts and theories used consist of advertising and advertising, social media, social media advertising, Youtube and Semiotics. Roland Barthes divided semiotics into two levels of symbols: denotation and connotation. The research paradigm is interpretive with a qualitative approach. The method of analysis uses Roland Barthes semiotics that look at the meanings of denotation, connotations and myths. The results showed the meanings of semiotics according to Roland Barthes, namely describing the meaning of denotation depicted in the background elements of the scene, body gestures and facial expression. The meaning of connotations is exposed by the background elements of the scene, fashion, color and nonverbal communication. The meaning of myth is illustrated by a high sense of concern for fellow human beings, when distance is not a problem to bring people far away.. Abstrak. Tujuan penelitian ini untuk mengkaji makna iklan Tokopedia “Mendekatkan Yang Jauh, Kirim Yang Bermakna” di YouTube menggunakan semiotika Roland Barthes. Konsep-konsep dan teori yang digunakan terdiri dari periklanan dan iklan, media sosial, iklan media sosial, YouTube dan semiotika. Roland Barthes membagi semiotika dalam dua level simbol yakni denotasi dan konotasi. Paradigma penelitian adalah interpretif dengan pendekatan kualitatif. Metode analisis menggunakan semiotika Roland Barthes yang melihat pada makna denotasi, konotasi dan mitos. Hasil riset menunjukkan makna-makna semiotika menurut Roland Barthes yaitu menjabarkan makna denotasi yang tergambarkan pada elemen latar adegan, gestur tubuh dan ekspresi wajah. Makna konotasi terpapar oleh elemen latar adegan, busana, warna dan komunikasi non-verbal. Makna mitos tergambarkan dengan rasa kepedulian yang tinggi terhadap sesama manusia, ketika jarak tidak menjadi masalah untuk mendekatkan orang-orang yang jauh.